Oxyprenylated Secondary Metabolites as Modulators of Lipid and Sugar Metabolism - Fiorito, Serena; Epifano, Francesco; Marchetti, Lorenzo; Palumbo, Lucia; Orhan, Ilkay E.; Sharifi-Rad, Majid; Genovese, Salvatore (Current Topics in Medicinal Chemistry, 2022)
O-Prenylcoumarins (3,3-dimethylallyl, geranyl-, farnesyl- and related biosynthetic derivatives) represent a class of rarely occurring natural compounds. Most of these secondary metabolites have been obtained from plant species belonging to the Rutaceae, Apiaceae, and Fabaceae families, and from fungi, and bacteria. In the last two decades, prenyloxycoumarins have been found to possess great potential in terms of pharmacological activities. The aim of this comprehensive review is to make a survey of the so far reported literature citations about these valuable phytochemicals and structurally related compounds about their modulatory properties of lipid and sugar metabolism. Literature data have been acquired from the main Internet database. Several oxyprenylated secondary metabolites have been surveyed. Among these, prenyloxycoumarins represented the main group displaying valuable effects as modulators of lipid and sugar metabolism. The title phytochemicals have been found in common fruits and vegetables already known to have beneficial effects, thus enforcing the nutraceutical role of these food plants. All compounds outlined in the present review article have a great potential in future for the prevention and management of acute and chronic metabolic disorders.
Keywords: Oxyprenylated coumarins